Assessment of NS1 gene-specific real time quantitative TaqMan PCR for the detection of Human Bocavirus in respiratory samples. (August 2017) - Ligozzi, Marco; Diani, Erica; Lissandrini, Federica; Mainardi, Rosanna; Gibellini, Davide
Abstract: Human Bocaviruses (HBoV) were associated with respiratory diseases. Here, we assessed a TaqMan ® -based PCR for the detection of all four HBoV subtype infections with a sensitivity up to 15 copies/reaction. To evaluate this assay on clinical samples, 178 nasopharyngeal aspirate specimens from pediatric cases were analyzed and HBoV genome was detected in 13 out of 178 patients with a viral load range between 1.6 × 10 3 and 9.4 × 10 7 copies/ml. These results indicated that this method could be used as an alternative technique for the diagnosis of HBoV infection. Highlights: TaqMan real time PCR specific for the amplification of HBoV NS1 was developed. This assay was tested for the diagnosis of HBoV infection in respiratory samples. This assay may be applied on the diagnosis of all four HBoV genotype infections.